ß1-adrenergic blockers preserve neuromuscular function by inhibiting the production of extracellular traps during systemic inflammation in mice - Bourcier, Camille H.; Michel-Flutot, Pauline; Emam, Laila; Adam, Lucille; Gasser, Adeline; Vinit, Stéphane; Mansart, Arnaud (Frontiers in Immunology, 2023)
Severe inflammation via innate immune system activation causes organ dysfunction. Among these, the central nervous system (CNS) is particularly affected by encephalopathies. These symptoms are associated with the activation of microglia and a potential infiltration of leukocytes. These immune cells have recently been discovered to have the ability to produce extracellular traps (ETs). While these components capture and destroy pathogens, deleterious effects occur such as reduced neuronal excitability correlated with excessive ETs production. In this study, the objectives were to determine (1) whether immune cells form ETs in the CNS during acute inflammation (2) whether ETs produce neuromuscular disorders and (3) whether an immunomodulatory treatment such as β1-adrenergic blockers limits these effects. We observed an infiltration of neutrophils in the CNS, an activation of microglia and a production of ETs following lipopolysaccharide (LPS) administration. Atenolol, a β1-adrenergic blocker, significantly decreased the production of ETs in both microglia and neutrophils. This treatment also preserved the gastrocnemius motoneuron excitability. Similar results were observed when the production of ETs was prevented by sivelestat, an inhibitor of ET formation. In conclusion, our results demonstrate that LPS administration increases neutrophils infiltration into the CNS, activates immune cells and produces ETs that directly impair neuromuscular function. Prevention of ETs formation by β1-adrenergic blockers partly restores this function and could be a good target in order to reduce adverse effects in severe inflammation such as sepsis but also in other motor related pathologies linked to ETs production.